Assessing performance of white endosperm testers with varying resistance reactions to Striga (Striga hermonthica) for evaluating resistant maize (Zea mays) inbred lines - Afolabi, S.; Menkir, A.; Oyekunle, M.; Abdullahi, U.; Gedil, Melaku A; Meseka, S.; Mengesha Abera, W. (Wiley, 2021)
Identification of testers is crucial for hybrid maize breeding programme. However, limited information is available about ideal testers for characterising the combining ability of Striga resistant maize inbreds. This study was conducted to assess the relative value of three inbred testers with varying resistance reactions to Striga for determining the combining ability of Striga resistant inbreds. Ninety testcrosses involving 30 Striga resistant inbreds and three testers were evaluated under artificial and natural Striga infestation and non-infested conditions at two locations for 2 years. Lines x tester interaction was significant (p ≤ .05) for most traits, indicating differential ranking of lines by the testers. The GCA effects of testers for most traits were high, highlighting the predominance of additive gene action in controlling the overall performance of testcrosses. The resistant and tolerant testers exhibited desirable GCA effects, broader testcross performance, greater genetic variances and consistent ranking of testcrosses under both growing conditions than the susceptible tester. These testers can be successfully used for identifying superior Striga resistant inbreds to develop high yielding and resistant hybrids for commercialization.